Analisis Struktur Pada Rangka Mobil Listrik Anobrain AR-1 Menggunakan Software Finite Element - Suhenda, Muhammad Basith Ayyasy; Gusniar, Iwan Nugraha; Dirja, Iman (Patria Artha Technological Journal, 2022)
In designing an electric car, of course, it requires a frame that works as a support for all the loads that are on it, for a frame construction itself it must have strength, light weight and have a good flexibility value. This frame structure test aims to find the value of stress, displacement, and safety factor on the car frame using finite element software, with a mass loading on the driver of 100 kg, seat load 0.8 kg, and the load of the motor and other supporting elements 62 kg. type of hollow pipe iron profile which has a size of 3/4 inch. In the theoretical calculation results obtained a maximum stress of 6312 x 107 N/m2. The material in the car frame is divided into 3 variations, namely Aluminum 6061 which has a material allowable stress of 1.375 x 108 N/m2 with a deflection value in the theoretical calculation of 7.933 x 10-1 mm and the results of simulation calculations are 7,483 x 10-1 mm has a safety factor value of 3,472 with an error ratio of 6%, ASTM A36 STEEL has a material stress stress of 1,250 x 108 N/m2 with a deflection value in the theoretical calculation of 2,736 x 10-1 mm and the calculation result is 2,560 x 10-1 mm has a safety factor value of 3.102 with an error ratio of 6.8%, st37 steel has a material allowable stress of 2.650 x 108 N/m2 with a deflection value in the theoretical calculation of 2,670 x 10-1 mm and the simulation results of 2,504 x 10-1 mm have a safety factor value of 6612 with the ratio of errors or errors is 6.6%.Keywords:Â  Analysis, kmli, frame, finite element.